2022
DOI: 10.1038/s41598-022-22818-5
|View full text |Cite
|
Sign up to set email alerts
|

Mapping human disease-associated enzymes into Reactome allows characterization of disease groups and their interactions

Abstract: According to databases such as OMIM, Humsavar, Clinvar and Monarch, 1494 human enzymes are presently associated to 2539 genetic diseases, 75% of which are rare (with an Orphanet code). The Mondo ontology initiative allows a standardization of the disease name into specific codes, making it possible a computational association between genes, variants, diseases, and their effects on biological processes. Here, we tackle the problem of which biological processes enzymes can affect when the protein variant is dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…DisGeNET [34] (version 7.0) collects the genetic basis of human diseases. DAR [35] provides disease-pathway and disease-gene relations.…”
Section: Data Sources To Construct Megakgmentioning
confidence: 99%
“…DisGeNET [34] (version 7.0) collects the genetic basis of human diseases. DAR [35] provides disease-pathway and disease-gene relations.…”
Section: Data Sources To Construct Megakgmentioning
confidence: 99%
“…The Disease And Reactome (DAR) database ( Savojardo et al, 2022 ) provides a wealth of information on enzymes, including their relationships with Reactome pathways, molecular interactions within the pathways, and tissue expression levels as recorded in the Human Protein Atlas ( Uhlén et al, 2015 ).…”
Section: Online Resources and Databases For Rare Diseasesmentioning
confidence: 99%
“…The dataset is enriched with experimentally proven impact of clinical mutations on interactions, TABLE 1 For each enzyme class, the table lists the number of enzymes associated with Orphanet RDs, the number of the corresponding Orphanet diseases, and the number of the corresponding Reactome roots and pathways. The data were derived from DAR database (Savojardo et al, 2022) and also with the non-clinical mutations which are found to impact protein functionality. So far, the dataset contains over 7,900 interactions involving about 2,500 interactors.…”
Section: Gene and Protein Network Databasesmentioning
confidence: 99%